STUDIES ON ARTIFICIAL ANTIGENS : III. THE GENETIC CONTROL OF THE IMMUNE RESPONSE TO HAPTEN-POLY-L-LYSINE CONJUGATES IN GUINEA PIGS - Levine, Bernard B. (The Rockefeller University Press, 1963)
The genetic transmission of the capacity to develop an immune response to hapten-polylysine conjugates was studied in guinea pigs. 82 per cent of the 22 offspring of 8 pairs of responder (guinea pigs which are capable of an immune response) parents were also responders, whereas, none of the 26 offspring of 9 pairs of non-responder parents were responders. None of 11 strain 13 guinea pigs and 100 per cent of 40 strain 2 guinea pigs were responders. These findings are consistent with the view that the capacity to respond immunologically to hapten-polylysine conjugates is genetically transmitted as a unigenic Mendelian dominant.